2013
DOI: 10.1128/aem.01693-13
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Phenotypic Characterization of Escherichia coli O26:H8 among Diarrheagenic E. coli O26 Strains Isolated in Brazil

Abstract: f Escherichia coli strains of serogroup O26 comprise two distinct groups of pathogens, characterized as enteropathogenic E. coli (EPEC) and enterohemorrhagic E. coli (EHEC). Among the several genes related to type III secretion system-secreted effector proteins, espK was found to be highly specific for EHEC O26:H11 and its stx-negative derivative strains isolated in European countries. E. coli O26 strains isolated in Brazil from infant diarrhea, foods, and the environment have consistently been shown to lack s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 63 publications
1
13
0
1
Order By: Relevance
“…Atypical EPEC (aEPEC) strains BA2103 (serotype O26:H11) and 2271-1/85 (serotype O26:HNM, where NM indicates nonmotile) were previously characterized by the eae +/EAF-/ bfpA - genetic profile, lack of production of BFP and production of the localized adherence-like (LAL) pattern on HEp-2 cells [ 5 , 6 , 39 ]. Molecular typing of fliC defined the H type of 2271-1/85 strain as H11 [ 39 ]. Binding ability to ECM of supernatant proteins from BA2103 was described elsewhere [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Atypical EPEC (aEPEC) strains BA2103 (serotype O26:H11) and 2271-1/85 (serotype O26:HNM, where NM indicates nonmotile) were previously characterized by the eae +/EAF-/ bfpA - genetic profile, lack of production of BFP and production of the localized adherence-like (LAL) pattern on HEp-2 cells [ 5 , 6 , 39 ]. Molecular typing of fliC defined the H type of 2271-1/85 strain as H11 [ 39 ]. Binding ability to ECM of supernatant proteins from BA2103 was described elsewhere [ 7 ].…”
Section: Methodsmentioning
confidence: 99%
“…A non-pathogenic K12 E. coli DH5α was included as a control strain [ 40 ]. Also, twenty O26:H11 aEPEC strains were employed in the fibronectin binding screening [ 5 , 39 ]. This study does not involve humans, human data or animals, since all strains employed herein belong to the Bacteriology Laboratory bacterial collection of Butantan Institute, São Paulo, SP, Brazil.…”
Section: Methodsmentioning
confidence: 99%
“…The aim of this work was to investigate the distribution of E. coli O26 genotypes within bovine feces and identify the pathogenic potential of Shiga toxin-negative and eae-positive strains that belong to the AEEC pathogroup. Recent findings in Brazil of E. coli O26 containing the H8 antigen belonging to EHEC and stx-negative strains led to the inclusion of this antigen in this study (45). Furthermore, antigen H11 and nonpathogenic antigen H32, commonly isolated in food products, were also tested (18,(45)(46)(47).…”
Section: Discussionmentioning
confidence: 99%
“…Recent findings in Brazil of E. coli O26 containing the H8 antigen belonging to EHEC and stx-negative strains led to the inclusion of this antigen in this study (45). Furthermore, antigen H11 and nonpathogenic antigen H32, commonly isolated in food products, were also tested (18,(45)(46)(47). Investigation of the H antigen revealed that all strains were positive for fliC H11 .…”
Section: Discussionmentioning
confidence: 99%
“…Cepas de aEPEC podem apresentar um repertório de virulência bastante heterogêneo, especialmente devido à plasticidade de seus genomas que permitem a aquisição de genes de virulência derivados de outros patotipos de E. coli diarreiogênicas ou que causam doenças extra-intestinas (ExPEC) (BANDO et al, 2009;HERNANDES et al, 2009). Deste modo, aEPEC pode carregar genes que codificam adesinas fimbriais e afimbriais (AFSET et al, 2006;GOMES et al, 2011;HERNANDES et al, 2011;SCALETSKY et al, 2009), enterotoxinas (DUTTA et al, 2015;HAZEN et al, 2017a;SILVA et al, 2014), hemolisinas (MAGALHÃES et al, 2011MURASE et al, 2012;PIAZZA et al, 2013) e uma série de proteínas autotransportadoras (ABREU et al, 2013;ABREU et al, 2016;RUIZ et al, 2014).…”
Section: Escherichia Coli Enteropatogênica (Epec)unclassified